The Implementation of Phenomenological Approach in Islamic Studies - Nisa, Lutfiyatun; Budianti, Tesya Arie; Tarianingsih, Tarianingsih; Aprianti, Baidiyah; Rif'iyati, Dian (STAI Publisistik Thawalib Jakarta, 2024)
Phenomenology emphasizes the understanding of religion through direct, prejudice-free, and neutral experiences. This approach seeks to uncover authentic meaning, going beyond preconceived ideas and limiting cultural frameworks. The aim of this study is to explain the application of the phenomenological approach in understanding religious phenomena by prioritizing religious experiences as they truly are. This research employs a literature study method with data collection techniques in the form of documentation, including analysis of literature related to phenomenological theory and practice within the context of religion. Research Findings: The phenomenological approach has two main characteristics: first, understanding another person’s religion from a neutral perspective and then attempting to reconfigure that religion based on the individual’s personal experiences and preferences. Second, a taxonomic framework should be developed to classify religious and cultural community phenomena. The true focus of religious phenomenology is the exploration of the essence, meaning, and fundamental structure of religious experience. Human religious experience possesses an irreducible essence that forms the basic structure of human religion. The phenomenological approach can be introduced in Islamic studies as an acceptable method for exploring Islam and includes practical examples commonly encountered in daily life. Conclusion: The phenomenological approach explains religious experience in a neutral, profound, and practical way to understand the essence and fundamental structure of human religion.